2021
DOI: 10.1111/soru.12334
|View full text |Cite
|
Sign up to set email alerts
|

LEADER and Spatial Justice

Abstract: Recent papers have argued that spatial justice should be pursued through a place-based approach, which enables local people to assert their own capacity to act and to pursue their own positive visions: an approach fundamental to LEADER. This paper considers the extent to which LEADER constitutes local action addressing spatial justice through a case study in England. Analysis of this case leads to questions about the extent to which apparent localism is constrained by 'government at a distance' and how this ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…All this calls into question the ability of the LEADER program to contribute to the well-being of disadvantaged rural areas or the potential of the financial instrument to help them achieve a higher level of development. As Shucksmith et al [34] state, the very endogenous development specific to the LEADER program can lead to an accentuation of inequalities. This is due to the opportunity to benefit from the LEADER program offered equally to developed and underdeveloped areas, although the latter do not have the same capacity to mobilize resources and form effective external relationships as the previous ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All this calls into question the ability of the LEADER program to contribute to the well-being of disadvantaged rural areas or the potential of the financial instrument to help them achieve a higher level of development. As Shucksmith et al [34] state, the very endogenous development specific to the LEADER program can lead to an accentuation of inequalities. This is due to the opportunity to benefit from the LEADER program offered equally to developed and underdeveloped areas, although the latter do not have the same capacity to mobilize resources and form effective external relationships as the previous ones.…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions underline their low efficiency in supporting severely disadvantaged rural areas, the main target of development programs, thus indicating a selective behaviour of the programs, but in favour of the already developed regions. According to Shucksmith et al [34], this selective behaviour seems to have been specific to the LEADER program at least until the end of the fourth funding period in Europe, as it has focused mainly on supporting the more active and developed communities in the detriment of the strongly disadvantaged groups. Most of these studies are analysing the results of the LEADER program at the level of some European countries such as Spain [10,[15][16][17][18]23,24,32,35], Germany [7,17], Italy [28,36], France [15,37,38], United Kingdom [30,32,34], or Denmark [13,39] that have benefited from this financial support since the first years of the implementation of the LEADER program, when experience in managing funds was low, which explains some of the mistakes in its implementation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, the shift towards place-based approaches runs the risk of undermining the redistributive top-down logic of policy interventions intended to enhance spatial justice. At the same time, there is often a need for critical scrutiny of the way local capacities are identified and strategic priorities for localities are set, as some of the case studies discussed in this special issue have shown (see Hämäläinen and Nemeth 2021;Keller and Virág 2021;Petrakos et al 2021, all in this issue; see also Shucksmith, Brooks, and Madanipour 2021). Contributions in this special issue provide evidence of some of the dilemmas and potential of place-based approaches, and help to understand their role in promoting territorial cohesion and spatial justice.…”
Section: The Place-based Approach In Eu Cohesion Policymentioning
confidence: 95%
“…Respective studies indicating the need to assess also the qualitative nature of assessing local action are taken up and discussed with regard to their relevance to influence by trans-national experiences. It should be underpinned that a critical reflection of existing (local, regional, national) views might be useful for considering new options, realizing new assets and engaging in local action with inclusive and just approaches (Shucksmith et al, 2020). In this regard it seems crucial to reveal through a small number of case studies of trans-national cooperation the potential and challenges of such collaboration activities, and the relevance for the overall conceptual perspective of the LEADER/CLLD programme.…”
Section: Methodological Approachmentioning
confidence: 99%
“…As "enabling" rural development cannot be achieved by standard approaches or general advices won't be sufficient for instigating actually "enabling" environments and contexts where participation, cooperation, trans-regional exchange, "learning" process and inclusion is a core value and indicator for the program's success (Shucksmith, 2018), including aspects of territorial balance as referred to in recent discourse on 'spatial justice' (Shucksmith et al, 2020). Assessment would have to build on an in-depth involvement for each different case highlighting the place-specific design, application and results (Midmore et al, 2010).…”
Section: Diversity and Social Innovation As Drivers For Rural Changementioning
confidence: 99%